The role of constructivist philosophy in arithmetic learning using the brainingcamp application - Elya Elya; Sri Tirto Madawistama (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This study aims to evaluate the impact of using the Brainingcamp application in improving the understanding of arithmetic concepts among fourth-grade students at Islamic Leader School in Tasikmalaya City through a constructivist approach. The research employs a case study approach with qualitative descriptive design, involving 22 students as research subjects during the first semester of the 2024/2025 academic year. Data were collected through classroom observations, written tests (pre-test and post-test), and interviews with students and teachers. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using descriptive statistics. The results show a significant improvement in students’ average scores after using Brainingcamp, with increases of 17.6% in addition, 18.8% in subtraction, 24.3% in multiplication, and 30.8% in division. Observations and interviews also reveal that students became more active, motivated, and collaborative during the learning process. The use of virtual manipulatives supports the principles of constructivism, aligning with Piaget’s and Vygotsky’s theories by providing opportunities for students to build their own understanding through visual exploration and social interaction. Based on these findings, Brainingcamp proves effective in enhancing both conceptual understanding of arithmetic and student engagement, although this study has limitations in terms of sample size, duration, and generalizability. Therefore, it is recommended to replicate the study with a larger and more diverse population and extend the duration of implementation in future research.